Catch-up immunisation for children in earthquake-affected areas of West Pasaman, Indonesia - Syawqi Rahmat; Fitry Yani Finny; Asrawati; Mariko Rinang (E3S Web of Conferences)
Children are a particularly vulnerable population when exposed to natural disasters and experience increased problems related to physical health, mental health and post-disaster learning. The conditions of displacement during a disaster will cause an increased risk of morbidity to mortality of infectious diseases and even potential outbreaks. The success of immunisation efforts at the scene of a disaster is a successful effort to reduce the mortality rate due to Immunisation Preventable Diseases. However, in emergency or disaster situations, there can be significant disruption or reduction in routine immunisation services, delays or temporary suspension of immunisation programmes. Immunisation achievements in West Pasaman Regency, especially in Kenagarian Kajai, still have not reached the target of forming herd immunity. The Covid 19 pandemic is one of the causes of low immunisation achievements and the earthquake could further reduce it. Efforts to achieve immunisation targets must also be made in a disaster situation, one of which is in the form of an immunisation catch-up program. We collaborated with various parties in Kenagarian Kajai, West Pasaman to conduct catch up immunisation through posyandu as an effort to ensure children in disaster locations still have the opportunity to get immunised according to the recommended immunisation schedule.